Ecological Effects of Water-level Fluctuations in Lakes - Wantzen, Karl M.; Rothhaupt, Karl-Otto.; Mörtl, Martin; Cantonati, Marco; G.-Tóth, Lászlo; Fischer, Philipp; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2008)
Most aquatic ecosystems have variable water levels. These water-level fluctuations (WLF) have multiple effects on the organisms above and below the waterline. Natural WLF patterns in lakes guarantee both productivity and biodiversity, while untimely floods and droughts may have negative effects. Human impacts on WLF have led to a stabilization of the water levels of many lakes by hydraulic regulation, untimely drawdown due to water use, or floods due to water release from hydropower plants in the catchments. This book provides a first review in this field. It presents selected papers on the ecological effects of WLF in lakes, resulting from a workshop at the University of Konstanz in winter 2005. Issues addressed here include the extent of WLF, and analyses of their effects on different groups of biota from microorganisms to vertebrates. Applied issues include recommendations for the hydrological management of regulated lakes to reduce negative impacts, and a conceptual framework is delivered by an extension of the floodpulse concept for lakes. Current impacts on water use, including increasing demands on drinking and irrigation water, hydropower etc., and climate change effects on WLF make this book an essential resource for aquatic ecologists, engineers, and decision-makers dealing with the management of lake ecosystems and their catchments.
Ecological effects of water-level fluctuations in lakes: an urgent issue -- Potential effects of water-level fluctuations on littoral invertebrates in lowland lakes -- Effects of water-level regulation on the nearshore fish community in boreal lakes -- Natural lake level fluctuation and associated concordance with water quality and aquatic communities within small lakes of the laurentian great lakes region -- Climate change and lakeshore conservation: a model and review of management techniques -- The impact of water-level regulation on littoral macroinvertebrate assemblages in boreal lakes -- Quantitative trends of zebra mussels in Lake Balaton (Hungary) in 2003–2005 at different water levels -- Patterns, origin and possible effects of sediment pollution in a mediterranean lake -- Temporal scales of water-level fluctuations in lakes and their ecological implications -- Effects of water-depth and water-level fluctuations on the macroinvertebrate community structure in the littoral zone of lake constance -- Flooding events and rising water temperatures increase the significance of the reed pathogen pythium phragmitis das a contributing factor in the decline of phragmites australis -- Leaf litter degradation in the wave impact zone of a pre-alpine lake -- Use of the water-level fluctuation analysis tool (Regcel) in hydrological status assessment of finnish lakes -- Mass mortality of the invasive bivalve Corbicula fluminea induced by a severe low-water event and associated low water temperatures -- An extension of the floodpulse concept (FPC) for lakes -- Effects of water-level fluctuations on lakes: an annotated bibliography.
Keywords: Environmental management; Aquatic ecology .; Ecosystems; Wildlife; Fish; Environmental Management; Freshwater & Marine Ecology; Ecosystems; Fish & Wildlife Biology & Management